Reward management : a handbook of remuneration strategy and practice - Armstrong, Michael 1928- (New Delhi : Kogan Page, 2008)
"This updated fifth edition of Armstrong's Handbook of Reward Management Practice contains new information on computerized reward management and new case studies. Additionally, Armstrong revised the chapters on pay evaluation, pay structures, merit pay, and executive pay to include new information. The online resources include questions, a glossary and bibliography, teaching notes, and PowerPoint slides for professors"--
"Armstrong's Handbook of Reward Management Practice is the definitive guide to understanding, developing and implementing effective reward. It is closely aligned to the CIPD's standard in reward management and is supported by online resources for both lecturers and students. Updated to reflect the practical implications of the most recent research and discussion on reward management, this new fifth edition includes a new chapter on computerized reward management, completely updated chapters on job evaluation, pay structures, merit pay and executive pay, and new case studies. As with all of Armstrong's texts, this truly bridges the gap between academic and practitioner and is, therefore ideally suited to anyone studying for a professional qualification in HR, of which Reward is often a core part, in particular the CIPD's intermediate and advanced level qualifications. The online resources which accompany the book include questions, a glossary, bibliography and case studies for students, and notes and PowerPoint slides for lecturers"--
Includes bibliographical references and index.
Keywords: Incentives in industry; Employee motivation; Compensation management; BUSINESS & ECONOMICS / Human Resources & Personnel Management